Factors affecting earnings management: current tax expenses, deferred tax liabilities, and deferred tax expenses - Saputra, Asep; Kuntadi, Cris (Gema Wiralodra, 2023)
Previous or relevant research is fundamental in a study or scientific article. Previous relevant research strengthens the theory and phenomena of the relationship or influence between variables. This article reviews the factors influencing earnings management, namely current tax, Deferred Tax Liabilities, and Deferred Tax Expenses, a literature study on tax accounting. This article aims to build a hypothesis on the influence between variables to be used in further research thesis literature review article results in e are: 1) the current tax burden affects earnings management; 2) current tax liabilities affect deferred tax; and 3) deferred tax expense affects earnings management.